2016
DOI: 10.1016/j.jns.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in acute stroke care organisation

Abstract: Background: Few studies have assessed regional variation in the organisation of stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Previous studies have shown large variations in the organisation of stroke care across hospitals which may compromise effective ourcomes, as significant associations between receipt of evidence-based care and clinical outcomes were reported in our international, multicentre, Head Positioning in acute Stroke Trial (HeadPoST) [7,14]. Despite acknowledging variations in stroke care pathways, access to ASU, and other aspects of stroke care [14,15], few studies have systematically quantified how the specific components of ASU care may differ across regions of the world [16]. Herein, we quantify the components of ASU care, within and across hospitals, in four participating income-grouped geographical regions for patients who participated in the HeadPoST.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown large variations in the organisation of stroke care across hospitals which may compromise effective ourcomes, as significant associations between receipt of evidence-based care and clinical outcomes were reported in our international, multicentre, Head Positioning in acute Stroke Trial (HeadPoST) [7,14]. Despite acknowledging variations in stroke care pathways, access to ASU, and other aspects of stroke care [14,15], few studies have systematically quantified how the specific components of ASU care may differ across regions of the world [16]. Herein, we quantify the components of ASU care, within and across hospitals, in four participating income-grouped geographical regions for patients who participated in the HeadPoST.…”
Section: Introductionmentioning
confidence: 98%
“…While ASU care is relatively well-defined in high resource settings, less attention has been given to its availability and appropriateness in low-and middle-income countries (LMICs), where most of the global burden of stroke occurs [12,13]. Previous studies have shown large variations in the organisation of stroke care across hospitals which may compromise effective ourcomes, as significant associations between receipt of evidence-based care and clinical outcomes were reported in our international, multicentre, Head Positioning in acute Stroke Trial (HeadPoST) [7,14]. Despite acknowledging variations in stroke care pathways, access to ASU, and other aspects of stroke care [14,15], few studies have systematically quantified how the specific components of ASU care may differ across regions of the world [16].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Having organized local stroke care protocols, established goals and quality improvement strategies, all have an important role in stroke care. 31 Unfortunately, considerable regional differences remain in optimal stroke care, including access to stroke units, 32 particularly in low resource settings. Such disparities require further urgent attention to reduce the burden of stroke, in particular in low and middle-income countries where fewer resources are available and stroke rates are increasing.…”
Section: Improving Stroke Systems Of Carementioning
confidence: 99%
“…22 Conversely, in low-income countries, where most of the global stroke burden exists, the lying flat position (and more prolonged immobilization) is widely applied due to use of simple non-mechanical beds. Taken together with other geographical variations in nursing practices and hospital care policies, 23 the manner in which acute stroke patients are nursed could be highly relevant to variable outcomes and adverse events from this critical illness across the world.…”
mentioning
confidence: 99%
“…The aim is to determine the comparative effectiveness (and safety) of the lying flat versus sitting up head position in patients with acute stroke. 23 Given uncertainty over the relevance of any treatment effects on a surrogate measure, such as increased CBF after AIS, 25,26 the study has been powered to determine effects on hard clinical endpoints assessed by trained personnel blind to treatment allocation. The use of broad inclusion criteria will allow an assessment of any heterogeneity of potential benefits (and harms) between AIS and ICH, and across particular subtypes of AIS, e.g.…”
mentioning
confidence: 99%